2006
DOI: 10.1038/emm.2006.61
|View full text |Cite
|
Sign up to set email alerts
|

Methionine synthase reductase polymorphisms are associated with serum osteocalcin levels in postmenopausal women

Abstract: Homocysteine (Hcy) is thought to play an important role in the development of osteoporosis and fracture. Methionine synthase reductase (MTRR) is an enzyme involved in the conversion of Hcy to methionine. We hypothesized that certain genetic polymorphisms of MTRR leading to reduced enzyme activity may cause hyperhomocysteinemia and affect bone metabolism. We therefore examined the associations of the A66G and C524T polymorphisms of the MTRR gene with bone mineral density (BMD) and serum osteocalcin levels in po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 31 publications
0
9
1
Order By: Relevance
“…Since miRNAs usually inhibit their target gene, this up-regulation of miR-143 is consistent with the downregulation of the Smad4 gene. Since, Mtrr has been found to have a significant correlation with osteocalcin levels and bone turnover, 105 it is interesting that we found a 2.4-fold decrease in fracture healing of alcohol-consuming animals.…”
Section: Developmentmentioning
confidence: 85%
“…Since miRNAs usually inhibit their target gene, this up-regulation of miR-143 is consistent with the downregulation of the Smad4 gene. Since, Mtrr has been found to have a significant correlation with osteocalcin levels and bone turnover, 105 it is interesting that we found a 2.4-fold decrease in fracture healing of alcohol-consuming animals.…”
Section: Developmentmentioning
confidence: 85%
“…In addition, hyperhomocysteinemia results in increasing production of oxidation products, homocysteine thiolactone and homocysteine mixed disulphides 4,5 , which could directly or indirectly damage bone. Some authors found that hyperhomocysteinemia was associated with serum osteocalcin levels in postmenopausal women 20 . However, the link was not evident in our participants (men and premenopausal women with type 2 diabetes).…”
Section: Discussionmentioning
confidence: 99%
“…Because of contradictory results with the studies, more studies are required to come to a final conclusion. The Hcy-induced fracture risk could be assessed by analyzing bone metabolism markers which are divided into bone formation (alkaline phosphatase, pro-collagen type I N and C-terminal peptides, osteocalcin) [15, 25, 2931], and bone resorption (collagen I, beta-crosslaps, urinary deoxypyridinoline crosslinks, tartrate resistant acid phosphatase 5b) [30, 32, 33]. However, metabolism anomalies arise after disturbance of normal axis between bone formation and resorption.…”
Section: Historical Perspective and Effect Of Homocystinuria On Bonementioning
confidence: 99%